INVESTIGATION OF POLYURETHANE, USED FOR THE PRODUCTION OF BIO-IMPLANTS, WITH THE HELP OF MODERN EXPERIMENTAL METHODS TO IMPROVE THE PERFORMANCE OF BIO-IMPLANTS - Beliaev, A.Yu. (Perm Federal Research Centre Journal, 2016)
The paper presents summary results of research works on the regional grant RFBR14-08-96003-r_ural_a. The object of the research is the issue of the polyurethane applicability as a material for the production of implants with a bioactive carbonized nanolayer. Increased requirements of biocompatibility, durability, strength and, what is rather important, the identity of the mechanical characteristics of replaced bio-objects are applied to such implants. Polyurethane is a very promising material for the production of bio-implants. However, at the moment there is no 6sufficient information about the elastic and strength properties of polyurethanes with a bioactive carbonized layer. In addition there is a necessity to study the micro- and nanostructure of the surface of the carbonized layer. The obtained data will help to determine the right combination of mechanical properties, which the material must have, to provide maximum similarity of the performance of the implant and the replaced object.